Protective role of resveratrol against cisplatin induced ototoxicity in guinea pigs - YUMUŞAKHUYLU, ALİ CEMAL; YÜKSEL, MERAL; ŞİRVANCI, SERAP (ELSEVIER IRELAND LTD, 2012)
Objective: The aim of this study was to evaluate the effectiveness of systemic administration of resveratrol against cisplatin-induced ototoxicity in guinea pigs. Materials and methods: Healthy guinea pigs (n = 24) were randomly divided into four groups. Group 1 (n = 6) received resveratrol + cisplatin, group 2 (n = 6) received 4% ethanol + cisplatin, group 3 (n = 6) received cisplatin, and group 4 (n = 6) received saline. Cisplatin was administered at a dose of 10 mg/kg/day on days 14 and 15 of the study. Resveratrol (10 mg/kg/day), 4% ethanol, and saline were administered throughout the study. Baseline auditory brainstem responses (ABR) (4 kHz, 8 kHz, and click stimulus) were determined for all groups. ABR was repeated 72 h after the last dose of cisplatin in order to record the threshold shifts. The ABR threshold shifts for the click stimulus, 4-kHz- and 8-kHz-frequency stimuli were compared after drug administration. After follow-up ABRs the animals sacrificed under deep sedation and their cochleae were removed. Left cochleae were immediately harvested for measurement of level of reactive oxygen species (ROS). Right cochleae were prepared for histological changes which were observed by scanning electron microscopy (SEM). Results: For the all stimulus, there was a significant threshold difference among the groups (p < 0.01). Group 3 had a significantly higher threshold shift at all stimuli when compared with groups 1 and 4. There was no significant threshold shifts in all stimuli between groups 2 and 3. The resveratrol-treated group 1 showed preservation of threshold in ABR (p <= 0.05). SEM showed that inner and outer hair cells were preserved in the group 1. Level of reactive oxygen species (ROS) were significantly higher in groups 2 and 3 compared with groups 1 and 4 (p <= 0.05). Conclusion: These results indicated that systemic administration of resveratrol afforded statistically significant protection to the cochlea of guinea pigs from cisplatin toxicity. Experimental dose of resveratrol injections may have a protective effect against cisplatin ototoxicity in guinea pigs. 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Resveratrol; Cisplatin; Ototoxicity; Auditory brainstem response; Reactive oxygen species; Scanning electron microscopy; ROUND WINDOW APPLICATION; D-METHIONINE; HAIR-CELLS; VITAMIN-E; ANTIOXIDANT; NEPHROTOXICITY; EXPRESSION; GROWTH; RATS